Assessing the prevalence of hand osteoarthritis in epidemiological studies. The reliability of a radiological hand scale. Issue 4 (1st April 2000) - Kessler, S; Dieppe, P; Fuchs, J; Stürmer, T; Günther, K P
Abstract : OBJECTIVE: The hands are often involved in the osteoarthritic disease process. A radiological grading scale is presented, derived from a published atlas, to assess the prevalence of hand osteoarthritis (OA) involvement in clinical and epidemiological studies and its reproducibility is studied. METHODS: This hand scale is based on the radiological feature "joint space narrowing", which represents the macromorphological process of cartilage loss. Osteophytes and sclerosis are less important unless seen in conjuction with joint space narrowing. Nine individual joints per hand (four proximal interphalangeal joints (PIP), four distal interphalangeal joints (DIP), first carpometacarpal joint (CMC-1)) are scored dichotomously for the presence of OA. To save time and to increase reliability a severity grading of radiological features is not performed. To determine inter-rater and intra-rater reliability of the individual joints and the presence of OA in two separate joint groups (⩾ 2 PIP or DIP and at least one CMC-1, used to define "generalised OA" in the ongoing Ulm Osteoarthritis Study) 50 pairs of anteroposterior hand radiographs were read by two investigators twice within one month. The κ coefficient was calculated to quantify the strength of associations. RESULTS: On average five minutes were needed to score one hand radiograph. Both raters were able to reproduce their own readings in all individual joints and for the presence of OA in two separate joint groups after one month. Reliability was highest for the PIP joints (κ: 0.56–1.00) it was slightly lower for the DIP joints (0.38–0.87), for the CMC-1 joints (0.58–0.69) and for OA in two separate joint groups (0.54). The values for inter-rater agreement were good as well, κ coefficients ranged from 0.52 to 0.92. CONCLUSION: This grading scale was shown to be reliable within and between readers for all the individual joints as well as for the presence of OA in two separate joint groups. Scoring a limited number of joints dichotomously makes this scale efficient and therefore useful for clinical and epidemiological trials, when dealing with large patient samples.